Lophoranina marestiana iz srednjeeocenskih flišnih plasti pri Gračišću v Istri - Mikuž, Vasja (Geologija, 2004)
In paper the crab of species Lophoranina marestiana (König, 1825) is described. It was found in a nummulitic olistostrome of Lower Lutetian flysch beds at the Gračišće hamlet near Pazin in Istria. Individuals of the describedtaxon are very rare in the locality.
Keywords: Croatia; Crustacea; eocen; fosili; Gračišće; Hrvaška; Istra; Istria; paleontologija; paleontology; raki; terciar